ANALISIS KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP LOYALITAS KONSUMEN PADA KILAT COFFEE MEDAN - Amsal Sanjaya Tambun; Aprinawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Coffee Shops have become a phenomenon and a part of the lifestyle of modern society. Coffee Shops are required to realize that customers are a central element in business continuity. One strategy commonly implemented is developing customer loyalty (consumers) as an effort to maintain the market and maintain the sustainability and profitability of the company. The study aims to determine the effect of product quality and service quality on consumer loyalty at Kilat Coffee Medan. This study used a quantitative method with a sample of 140 respondents. The data obtained were analyzed using a statistical formula, namely by using the Smart Partial Least Square (PLS) program version 4.1.0.9. Based on the results of statistical tests, it can be concluded that product quality has a positive and significant effect on consumer loyalty with a value (P-value 0.00 < 0.05) and (T-statistic 3.736 > 1.96) and service quality has a positive and significant effect on consumer loyalty with a value (P-value 0.00 < 0.05) and (T-statistic 2.496 > 1.96).